THE INFLUENCE OF REWARD AND PUNISHMENT ON EMPLOYEE PERFORMANCE WITH HR QUALITY AS AN INTERVENING VARIABLE IN THE MEDAN RELIGIOUS TRAINING CENTER - Saputra, Hairul; B, Mesra (Penerbit Lafadz Jaya, 2023)
The existence of this research is to prove research and the influence of Reward and Punishment on Employee Performance with HR Quality as an intervening variable with a quantitative research type. The research location is at the Medan Religious Education and Training Center. The population of this research is 72 employees and uses a saturated sample because the population is all sampled. Data collection by distributing questionnaires and primary data sources is also used in this research model using analytical tools and calculation tools using Smart PLS. The results of this research are. HR quality has a positive and significant effect on performance with an original sample value of 0.179 and a P value of 0.011. Punishment has a negative and insignificant effect on employee performance at the Medan Religious Training Center. Punishment has a positive and significant effect on employee performance. Punishment has a positive and significant effect on HR Quality. Reward has a positive and significant effect on Employee Performance. Rewards have a positive and significant effect on HR Quality. Punishment has a positive and insignificant effect on Employee Performance through HR Quality with the original sample of 0.051 and a P value of 0.086, meaning HR Quality is not an intervening variable. Reward has a positive and significant effect on Employee Performance through HR Quality with the original sample of 0.125 and P value 0.011, meaning HR Quality can becomes an intervening variable because it can influence employee rewards and performance.